FEATURES OF THE STRUCTURE AND FORMATION OF THE KAMCHATKA CANYON (THE PACIFIC MARGIN OF KAMCHATKA) - V. L. Lomtev (Геодинамика и тектонофизика, 2018)
The measurement data on the Kamchatka Canyon, including the block diagram, a set of echograms, the longitudinal profile of the canyon, and the bathymetric map, and the continuous seismoacoustic profiling data (CSP) has been reinterpreted. The study covers the shelf and the upper and middle parts of the continental slope. Regional gas-saturated strata have been discovered in the Cenozoic cover of the shelf and the continental slope, as well as in the block landslides of the sedimentary cover on the left (~55 km long, the western slope of the Kamchatka Cape) and right (more than 25 km long, the Kamchatka river delta front) sides of the canyon. Hanging landslides on the left side are associated with a 100–150 m increase in the depth of the canyon. On the middle slope, there is a large (28 km long) block landslide and its almost compensated paleochannel. The sub-latitudinal turn and the displacement of the canyon mouth to the north by 70 km is related to uplifting of the ridge-barrier in the Middle Pleistocene – Holocene. Based on the measurement and CSP data, it becomes possible to contour landslides on the sides of the Kamchatka Canyon, select the most hazardous locations (hanging landslides on the upper slope) for numerical modeling of potential landslide-related tsunami, and develop recommendations pertaining to construction of a new international sea port in the town of Ust-Kamchatsk.